(untitled) (CIPEEX, 2025)
Introduction: Diabetic foot is a common complication of diabetes mellitus, characterized by infections, ulcers, and necrosis in the lower limbs, increasing the risk of amputation. Patients with the disease are more vulnerable to developing these lesions. In this context, the nursing team’s role is crucial for early detection, prevention, and appropriate referral. Objective: To report the experience of nursing monitoring in the care of a patient with diabetes mellitus and a severe skin lesion on the lower limb. Methods: This is an experience report carried out in a Primary Health Care Unit in Carmo do Rio Verde, Goiás, Brazil, between June 16 and July 11, 2025. Data were obtained from nursing consultations and electronic health records. The patient was followed for approximately three to four times per week, on different days (June 16- Monday; June 23 – Monday; June 27 – Friday; June 28 – Saturday; June 30 – Monday; July 2 – Wednesday; and July 11 – Friday). The nursing actions included wound assessment, dressing, administration of prescribed medications, monitoring blood pressure and blood glucose, patient education and coordination of referral to vascular surgery. Experience report: The nurse worked in the care of a diabetic patient with a severe lower limb lesion, performing dressings, administering medications, clinical monitoring, and referring patients for vascular surgery. Despite the progression to amputation of two toes, nursing monitoring after hospital discharge ensured self-care guidance, glycemic control, and prevention of further complications. Conclusion: This experience report highlights the importance of nursing in the care of skin lesions in diabetic patients, from the initial assessment to specialist referral, reducing complications and thus promoting a better quality of life for the patient.